Islamic Educational Values Reflected in the Attitude of Qona’ah: A Conceptual Library-Based Analysis - M. Saifuddin Al-Huda; Mudzakkir Ali; Nur Cholid; Ifada Retno Ekaningrum (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Despite the continued development of Islamic education, the internalization and practical understanding of Islamic educational values among learners have not always progressed in a balanced manner. This condition indicates a gap between educational advancement and value-based character formation. This study aims to conceptually examine the Islamic educational values embedded in the attitude of qona’ah and to clarify its relevance to character education within Islamic educational contexts. The research employs a qualitative library research method, drawing on classical and contemporary sources in Islamic education, ethics, and spirituality. Data were analyzed using a descriptive-analytical approach to identify key conceptual themes related to qona’ah as an educational value. The findings reveal that qona’ah represents an integrative value encompassing faith (aqidah), moral conduct (akhlaq), and normative guidance (shari‘ah), which together shape attitudes of simplicity, gratitude, reliance on Allah (tawakkal), self-control, and responsible engagement with material life. Conceptually, qona’ah functions as a foundation for developing balanced individuals who are able to harmonize spiritual consciousness with social and material responsibilities. This study contributes to Islamic educational discourse by offering a coherent conceptual framework that positions qona’ah as a strategic value for character education, thereby reinforcing the integration of spiritual objectives and educational practice in Islamic education.